Application of Personal data protection on electronic signatures in Indonesia - Viola Meiryan Azza; Hartana Hartana; G.nyoman Tio Rae (Publikasi Indonesia, 2024)
The Industrial Revolution 4.0 and digital transformation have brought significant changes in various aspects of life, including the business and administrative world. This revolution, driven by digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and cloud computing, enables automation in various industrial sectors and increases efficiency and productivity. This study aims to analyze the process of collecting, processing, and using personal data in using electronic signatures in Indonesia and knowing the compliance and legal consequences of personal data protection violations in using electronic signatures in Indonesia. This research approach is juridical normative. The research found that although the use of electronic signatures has increased rapidly during the COVID-19 pandemic, many challenges are still faced. Electronic signatures are often considered prestigious and challenging, although they have been widely used in signings by notaries. The author realizes that although much progress has been made, there is still room for improvement in adopting and understanding electronic signatures in Indonesia.